The Girl Who Played with Fire - Stieg Larsson 1954-2004; Reg Keeland 1943- (UK Maclehose Press, 2009)
On the eve of Mikael Blomkvist's story about sex trafficking between Eastern Europe and Sweden, two investigating reporters are murdered. And even more shocking for Mikael Blomkvist: the fingerprints found on the murder weapon belong to Lisbeth Salander--the troubled, wise-beyond-her-years genius hacker who came to his aid years before
Contains an excerpt from: The girl who kicked the hornet's nest. . translated from the Swedish by Reg Keeland . Issue Two Millennium Magazine
Keywords: Literature (3GdCOHs; General -- Fiction; Human trafficking; Murder -- Investigation -- Fiction; Hackers -- Sweden -- Stockholm -- Fiction